Creating a healthy Wirobrajan community from an early age through psychoeducation and early detection of people with mental disorders - Aminullah, Moh; Hidayah, Nurul; Phalevi, Jefri Reza (Community Empowerment, 2021)
Public concern for mental health problems is still very minimal, including in the Wirobrajan neighborhood, Yogyakarta, Indonesia. Wirobrajan Public Health Center as a public health facility has carried out various kinds of health education activities. However, the results were not optimal considering this requires the participation of the community in paying attention to health in the family environment. The mental health early detection movement is one of the factors for preventing mental health problems in the family. The purpose of this activity is to conduct psychoeducation and early detection of people with mental disorders (ODGJ) in the Wirobrajan environment. The method used was a cross-sector mini workshop in the form of ODGJ socialization, inauguration of the alert village decree and counseling on the role of families in preventing ODGJ recurrence. The results of the activity showed that mental health cadres had a better understanding of the concept, causes, and treatment of mental disorders, as well as the role of family and the environment in ODGJ. Thus, the cadres will understand more about people with mental disorders and have new abilities related to early detection of mental health.